2012
DOI: 10.1074/jbc.m112.364208
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Profile and Metal-ion Selectivity of Human Divalent Metal-ion Transporter-1

Abstract: Background: DMT1 plays essential roles in iron homeostasis, but questions remain about which other metals this transporter serves. Results: DMT1 exhibits substrate selectivity Cd 2ϩ Ͼ Fe 2ϩ Ͼ Co 2ϩ , Mn 2ϩ Ͼ Ͼ Ni 2ϩ , VO 2ϩ , Zn 2ϩ . Conclusion: DMT1 is an iron-preferring transporter that does not transport copper. Significance: These findings will help in predicting the contribution of DMT1 to absorption and cellular uptake of metal ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
200
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 227 publications
(208 citation statements)
references
References 65 publications
7
200
1
Order By: Relevance
“…1) Previous studies demonstrated that Ctr1 is a primary high-affinity Cu ϩ transporter in mammals, particularly within the intestine; however, a Ctr1-independent transport activity has been detected in Ctr1 Ϫ/Ϫ mouse embryonic fibroblasts (33). 2) Whereas we previously found no evidence that copper is a transported substrate of DMT1 in vitro (27), others have measured copper transport in vitro and concluded that DMT1 can transport Cu ϩ or Cu 2ϩ (1,2,16,29,34). Conversely, in two of the studies just cited, investigators proposed that Ctr1 is also capable of transporting Fe 2ϩ (16,34), so we also examined the expression of Ctr1 in the intestinal DMT1 int/int mouse.…”
mentioning
confidence: 42%
See 2 more Smart Citations
“…1) Previous studies demonstrated that Ctr1 is a primary high-affinity Cu ϩ transporter in mammals, particularly within the intestine; however, a Ctr1-independent transport activity has been detected in Ctr1 Ϫ/Ϫ mouse embryonic fibroblasts (33). 2) Whereas we previously found no evidence that copper is a transported substrate of DMT1 in vitro (27), others have measured copper transport in vitro and concluded that DMT1 can transport Cu ϩ or Cu 2ϩ (1,2,16,29,34). Conversely, in two of the studies just cited, investigators proposed that Ctr1 is also capable of transporting Fe 2ϩ (16,34), so we also examined the expression of Ctr1 in the intestinal DMT1 int/int mouse.…”
mentioning
confidence: 42%
“…We concluded that intestinal DMT1 is not required for zinc homeostasis, an anticipated outcome since 1) Zn 2ϩ is a weak DMT1 substrate in vitro, relative to Fe 2ϩ (Ref. 27), and 2) ZIP4, a metal ϩ/ϩ (gray) and DMT1 int/int (black) mice as a function of time after the oral radiotracer dose. Each plot depicts the data for an individual mouse.…”
Section: G642 Role Of Intestinal Dmt1 In Metal Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…The H ϩ gradient that drives DMT1-mediated iron uptake is generated by intestinal brushborder Na ϩ /H ϩ exchanger 3 (NHE3) (12). DMT1 transports only Fe 2ϩ , but most dietary iron is Fe 3ϩ (13); hence, a reduction step is needed before iron transport by DMT1. This activity is generally thought to be mediated by the ferrireductase duodenal cytochrome B (DCYTB 2 ; CYBRD1) located at the apical membrane of enterocytes (14).…”
Section: Dietary Iron Absorption By the Enterocytementioning
confidence: 99%
“…Nramps are generally thought to function as metal-proton symporters (1) and are able to bind and/or transport a wide range of divalent transition metal substrates, including the biologically useful metals Mn 2+ , Fe 2+ , Co 2+ , Ni 2+ , Cu 2+ , and Zn 2+ , as well as the toxic heavy metals Cd 2+ , Pb 2+ , and Hg 2+ (4,(9)(10)(11)(12)(13). Nramps do discriminate against the divalent alkaline earth metal ions Mg 2+ and Ca 2+ (9,14), which are typically several orders of magnitude more abundant than the transition metals (15).…”
mentioning
confidence: 99%